Optical and acoustic metamaterials: superlens, negative refractive index and invisibility cloak. (21st July 2017) - Wong, Zi Jing; Wang, Yuan; O'Brien, Kevin; Rho, Junsuk; Yin, Xiaobo; Zhang, Shuang; Fang, Nicholas; Yen, Ta-Jen; Zhang, Xiang
Abstract: Metamaterials are artificially engineered materials that exhibit novel properties beyond natural materials. By carefully designing the subwavelength unit cell structures, unique effective properties that do not exist in nature can be attained. Our metamaterial research aims to develop new subwavelength structures with unique physics and experimentally demonstrate unprecedented properties. Here we review our research efforts in optical and acoustic metamaterials in the past 15 years which may lead to exciting applications in communications, sensing and imaging.